HUBUNGAN ANTARA KECERDASAN EMOSIONAL, KEMANDIRIAN BELAJAR DAN KREATIVITAS BELAJAR DENGAN HASIL BELAJAR MATEMATIKA - Wulandari, Ni Komang Hita; Puspadewi, Kadek Rahayu; Noviyanti, Putu Ledyari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2021)
This correlational research aims to determine the relationship between emotional intelligence, independent learning and learning creativity with the mathematics learning outcomes of grade VII students of SMP Negeri 1 Blahbatuh. Data collection was carried out by means of questionnaires and tests. The sample used is a number of 80 people who are determined by the cluter random sampling technique. Hypothesis test used is simple and multiple regression with a significance level of 0.05. The results of this study indicate that there is a significant relationship between emotional intelligence and mathematics learning outcomes, the relative contribution is 46%. There is a significant relationship between independent learning and mathematics learning outcomes, the relative contribution is 39%. There is a significant relationship between creativity and mathematics learning outcomes, the relative contribution is 64%. There is an influence between emotional intelligence, independent learning and learning creativity with mathematics learning outcomes of students with a relative contribution of 62%.